Cultural Thought in the Caribbean? Arts’ Theory in Cuba, And Its Epistemic Status from a Historical Sociology of Scientific Knowledge Perspective - Arencibia Coloma, Yaneidys (Cultural Arts Research and Development, 2022)
Although History of Art studies within academia, began in the late thirties of the Twentieth Century, Arts’ Theory in Cuba has been an underdeveloped discipline. For this paper, we use the Sociology of Scientific Knowledge in its historical perspective, as a tool for analyzing Jorge Mañach’s cultural thought. This was one of the most important Cuban intellectuals of his time, who wrote some of the most notorious essays of Cuban Literature. We analyze his cultural essays, and also, the cultural institutions, intellectual initiatives and networks that supported his theoretical ideas. Essentially, the early Cuban 20th century reproduced some of the colonial matrix of power but, surprisingly, the Mañach’s theories featured relative epistemic autonomy and, therefore, decolonial thinking features yet to be studied. Therefore, we place the focus on the social conditions and cultural structures that might have enhanced the Cuban cultural thought in order to show its epistemic status.